2017
DOI: 10.1038/s41598-017-10316-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of butenolide regulatory system controlling secondary metabolism in Streptomyces albus J1074

Abstract: A large majority of genome-encrypted chemical diversity in actinobacteria remains to be discovered, which is related to the low level of secondary metabolism genes expression. Here, we report the application of a reporter-guided screening strategy to activate cryptic polycyclic tetramate macrolactam gene clusters in Streptomyces albus J1074. The analysis of the S. albus transcriptome revealed an overall low level of secondary metabolism genes transcription. Combined with transposon mutagenesis, reporter-guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…In a BLAST survey, we found one to three afsAlike genes in each of nine Streptomyces genomes (Niu et al, 2016). In another study, BLAST search for homologs of AfsA from S. griseus within the actinobacteria genomes available from public databases showed that AfsA-like proteins are present in most actinomycetes (Ahmed et al, 2017). The widespread distribution of GBLs was further confirmed by using VB-and IM-2-deficient strains as indicators to examine VB and IM-2 distribution.…”
Section: Five Major Classes Of Hormone-like Signaling Moleculesmentioning
confidence: 69%
“…In a BLAST survey, we found one to three afsAlike genes in each of nine Streptomyces genomes (Niu et al, 2016). In another study, BLAST search for homologs of AfsA from S. griseus within the actinobacteria genomes available from public databases showed that AfsA-like proteins are present in most actinomycetes (Ahmed et al, 2017). The widespread distribution of GBLs was further confirmed by using VB-and IM-2-deficient strains as indicators to examine VB and IM-2 distribution.…”
Section: Five Major Classes Of Hormone-like Signaling Moleculesmentioning
confidence: 69%
“…Similar to the case of compound 5, these three butenolides have also been isolated from marine-derived Streptomyces strains (17)(18)(19). In addition, compound 4 was recently identified in a genetically modified S. albus strain (20). However, compounds 2, 3, and 5 have never been isolated from S. albus J1074.…”
Section: Resultsmentioning
confidence: 80%
“…However, the in vivo function of compounds 2 to 5 in the original producer, S. albus J1074, still remains obscure, because no metabolite changes, other than those of compounds 2 to 5, were observed in the aco disruptant ( Fig. 3), although compound 4 was identified from a disruptant of a putative transcriptional regulatory gene (XNR_3174) and is probably involved in the production of tetramate macrolactams, candicidins, and antimycins A (20). These findings suggest that compound 2 and the other butenolide compounds, 3 to 5, are new members of the butenolide-type Streptomyces hormones and are likely to be "one-way" interspecies signaling molecules from S. albus J1074 to S. avermitilis, unlike in the case of SCB3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations